Antibacterial activity assessment of extract ethanol Bauhinia forficata L. / Avaliação da atividade antibacteriana de extrato etanólico da Bauhinia forficata L. - Felipe Lima Farias; Luana Luzia Santos Pires; Rubenício Izidro da Silva Júnior; Jessé Marques da Silva Júnior Pavão; Thiago José Matos-Rocha; Aldenir Feitosa dos Santos (Universidade Estadual de Alagoas, 2018)
Several scientific researches seek to find plant extracts that have curative and prophylactic potential for different pathologies. Currently, very few therapeutic options due to increased bacterial resistance, make necessary the search for new antimicrobial agents from plant extracts and other natural products are applied as pharmaceuticals, mainly in Brazil offering an immense biodiversity. Therefore, the objective was to identify the antimicrobial activity of Forficata bahuina and evaluate the smallest inhibitory concentration in clinical standard strains and isolates of multiresistant hospital origin. To the discovery of the antibacterial potential were used sheets Bahuinia forficata (Mororó/cow Pata). The antibacterial activity of the extract was analyzed by the microdilution broth method, wherein the inoculum was prepared to a concentration of 5 x 105 CFU / mL, from 0.5 McFarland suspension (1.5 x 108 CFU/mL) obtained from fresh colonies of selected bacteria. crude leaf extract, showed broad antibacterial activity against the three multiresistant bacteria of nosocomial origin, thus ensuring an experimental analytical evidence of great potential, allowing the detailed study to find new antibacterial agents of natural origin.